Life cycle cost analysis of an innovative nanofluid assisted photovoltaic thermoelectric air conditioner for energy efficiency enhancement in buildings - Balaji Bakthavatchalam; Ghassan F. Al-Doori; Salem Algarni; Talal Alqahtani; Reji Kumar Rajamony; Khairul Habib; Omar A. Hussein; Surendra D. Barewar (Case Studies in Thermal Engineering)
This study presents a comprehensive life cycle cost analysis of a novel Photovoltaic - Nanofluid Assisted Thermoelectric Air Conditioner aimed at enhancing energy efficiency and reducing emissions in building applications. The objective is to evaluate the economic and environmental performance of the Photovoltaic - Nanofluid Assisted Thermoelectric Air Conditioner system under tropical climatic conditions, using variables such as initial capital cost, operational cost, energy savings, carbon emission reduction, and payback period. The study takes into account the whole life cycle cost of the system, which includes purchase, installation, and operation, as well as retrofitting. Results indicate that the Photovoltaic - Nanofluid Assisted Thermoelectric Air Conditioner system significantly reduces operational cost by 91.16 USD compared to a conventional 1-ton split air conditioner, with an associated CO2 emission reduction of 68.88 tons. However, the payback period required to offset the higher initial investment is estimated at 39.74 years. Overall, the integration of nanofluids and thermoelectric modules with photovoltaic technology offers a sustainable pathway for advancing energy-efficient and low-emission buildings.